2020
DOI: 10.1002/ail2.16
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing and understanding inherent features in SD‐OCT for the progression of age‐related macular degeneration using deconvolutional neural networks

Abstract: To develop a convolutional neural network visualization strategy so that optical coherence tomography (OCT) features contributing to the evolution of age-related macular degeneration (AMD) can be better determined. We have trained a U-Net model to utilize baseline OCT to predict the progression of geographic atrophy (GA), a late stage manifestation of AMD. We have augmented the U-Net architecture by attaching deconvolutional neural networks (deconvnets). Deconvnets produce the reconstructed feature maps and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Feature maps were obtained based on the self-attended mechanism as described above for the visualization of significant self-attended CNN signals. Additionally, image features for the regular U-Net were reconstructed and visualized via transposed convolutions replacing the standard convolutions by deconvnet as described in 30 , 31 . The reconstruction blocks operated in reverse, so that the inputs to the reconstruction blocks were first passed through the activations before the transposed convolutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feature maps were obtained based on the self-attended mechanism as described above for the visualization of significant self-attended CNN signals. Additionally, image features for the regular U-Net were reconstructed and visualized via transposed convolutions replacing the standard convolutions by deconvnet as described in 30 , 31 . The reconstruction blocks operated in reverse, so that the inputs to the reconstruction blocks were first passed through the activations before the transposed convolutions.…”
Section: Methodsmentioning
confidence: 99%
“…There are in general two major types of attention mechanisms related to CNNs, categorized as trainable or non-trainable (i.e., post-hoc attention). Early efforts in exploration of attention mechanisms were more focused on post-hoc attention, for example, the heatmap visualization approaches via multi-layered deconvolutional network (deconvnet) 30 , 31 and via class activation mapping (CAM) 32 , 33 . Such post-hoc attention mechanisms helped visualize which parts in an image an already-trained CNN model deems important.…”
Section: Introductionmentioning
confidence: 99%
“…Visualization methods aim to produce “visual explanations” for decisions of CNN-based models to make them more transparent and explainable 38 . In order to build trust in intelligent systems a number of visualization methods have been proposed recently so that the input stimuli that excite CNNs could be made visually transparent 39 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, previous work in our group has demonstrated that such deep learning methods are able to detect GA in late stage AMD 8 and identify known baseline AMD biomarkers 6 . Further, our group has demonstrated that the combination of deconvolutional networks with a U-Net architecture 8 , 9 can reveal features most salient for anticipating the progression of AMD 7 . A modified U-Net model was trained to predict GA progression from en-face projections of OCT volumes with ground truth labels provided by annotated FAF images from a follow-up visit.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, there has been work towards applying deep learning methods to identify and visualize AMD baseline biomarkers 5 7 and AMD late stage atrophy 8 in SD-OCT and FAF images that can diagnose AMD. Deep learning—an objective artificial intelligence approach, has an advantage over traditional machine learning methods in that it learns directly from data so there is no need to manually designate features.…”
Section: Introductionmentioning
confidence: 99%